O tempo nos "Discorsi" de Maquiavel - Manoel de Almeida Neto (1999)
The present dissertation intends to discuss the notion of Time in the Machiavellis Discorsi Sopra la Prima Deca di Tito Livio highlighting the retake the autor makes of the circular conception of Plato and Polybio, in the Renascence context, in order to break with the linear image of time valide for the Middle Ages, distinctively christian, and expose, under an original perspective, the impasses recurring from the politics, specially the one related to the temporal maintenance of a regime. It will also be focalized the interpretation Machiavelli makes of the role of humans desires in the constitution, maintenance and corruption of a regime, and its relation to the inexorability of the time upon political forms. At last, it will be discussed the alternatives he proposes to contain the challenges imposes by the Fortune to the governments. These political new modes and orders, presented by the florentin under the light of the Roman Republic and specially characterized by the adoption of a mixed government capable of administrating the conflicts between the appettiti coming from the people, from the monarcs and aristocrats through a process of continuous foundation would allow to the regimes to be maintained in time and to attain to liberty.